The Moderation Role of Corporate Governance on Tax Aggressiveness - Sasmita, Djenni; Hasanudin, Agus Ismaya; Hanifah, Imam Abu; Januarsi, Yeni (International Review of Management and Marketing, 2025)
The study examines how tax aggression is affected by firm size, capital intensity, and institutional ownership with corporate governance acting as a moderating factor. Manufacturing firms that were listed between 2018 and 2022 on the Indonesia Stock Exchange comprise the study’s population. The population is 214 firms. 62 firms were chosen as research samples. Multiple regression analysis is the approach used for data analysis. The findings suggest that tax aggression is not a function of firm size. Tax aggressiveness is significantly impacted by institutional ownership and capital intensity. Corporate governance factors, however, do not seem to be able to increase the relationship between tax aggression and firm size, capital intensity, and institutional ownership. This is due to the lack of strength or effectiveness of existing corporate governance mechanisms, as well as certain company policies or management practices that may limit the moderating impact of corporate governance.